Формування компетенцій майбутніх фахівців первинної медичної допомоги при вивченні статистики та біофізики у медичному університеті - Строгонова, Тетяна Василівна; Бондар, М. В.; Точиліна, Тетяна Миколаївна; Strohonova, T. V.; Bondar, M. V.; Tochylina, T. M. (My University, 2022)
Стаття присвячена аналізу актуальних компетентностей фахівців первинної медичної допомоги зі статистики та фізики в процесі навчання у системі медичної освіти. Реформа первинної ланки медичної допомоги змінила роль та місце сімейного лікаря у системі надання медичної допомоги населенню. В епідемічній ситуації навантаження на лікарів суттєво зросло, адже до них насамперед звертаються пацієнти з підозрою на COVID-19. Дуже часто саме сімейні лікарі вимушені були працювати в умовах невизначеності, вони стикались із незнайомими, раніше не описаними ситуаціями. В таких ситуаціях професійна компетентність лікаря визначається тільки його здібністю критично мислити та приймати рішення, що базуються на знаннях фундаментальних законів. Авторами проаналізовано літературні джерела та використано метод порівняльно-історичного аналізу. Критичне мислення формується з перших днів навчання лікаря та закладається у курсі природно-наукових дисциплін – фізики, що формує науковий світогляд студента, та математики, що надає інструменти аналізу кількісних відношень у світі. У часи пандемії зросла потреба серед лікарів у статистичних інструментах обробки інформації. У зв’язку з цим автори пропонують розширити та доповнити перелік існуючих компетентностей зі статистики та біофізики, що включено у робочі програми дисциплін. На думку авторів, це дозволить підвищити компетентність майбутніх фахівців первинної медичної допомоги. Метою наступних досліджень є розробка навчально-методичних рекомендацій з проведення практичних занять для формування зазначених компетентностей. Article by associate professors of Zaporizhzhia State Medical University Strogonova T.V., Tochilina T.M. and a doctor of the highest category of KNP "Zaporizhzhia Center for Primary Health Care No. 5" Ph.D. Bondar M. V. "Formation of competencies of future specialists in primary care in the study of statistics and biophysics at the Medical University" is devoted to the analysis of current competencies of primary care professionals in statistics and physics in the process of learning in the medical education system. The reform of primary health care has changed the role and place of the family doctor in the system of providing medical care to the population. In the epidemic situation, the workload of doctors has increased significantly, as they are primarily approached by patients with suspected COVID-19. Very often, it was family doctors who were forced to work in conditions of uncertainty, where they faced situations unfamiliar, not previously described. In such situations, a doctor's professional competence is determined only by his ability to think critically and make decisions based on knowledge of fundamental laws. The authors analyzed the literature and used the method of comparative and historical analysis. Critical thinking of the doctor is formed from the first days of training and is laid in the course of natural sciences - physics, which forms the scientific worldview of the student and mathematics, which provides tools for analyzing quantitative relations in the world. During the pandemic, there was a growing need among physicians for statistical information processing tools. In this regard, the authors propose to supplement the list of special competencies. The authors propose to expand and supplement the list of existing competencies in statistics and biophysics, which are included in the work programs of the disciplines. According to the authors, this will increase the competence of future primary care professionals. The purpose of further research is to develop educational and methodological recommendations for conducting practical classes for the formation of these competencies.
Formation of competences of future primary medical care specialists in studying statistics and biophysics at the medical university
Keywords: компетенції; система медичної освіти; біофізика; сімейний лікар; первинна медична допомога; COVID-19; competencies; system of medical education; biophysics; family doctor; primary care